Thermophysical Modeling of the Vaporization Process in a Motive Nozzle with a Profiled Supersonic Part - Serhii Sharapov; Danylo Husiev; Volodymyr Klymenko; Ivan Pavlenko; Dobrochna Ginter-Kramarczyk; Andżelika Krupińska; Marek Ochowiak; Sylwia Włodarczak (Energies)
In this article, thermophysical modeling of boiling flows in the motive nozzle is carried out for a liquid–vapor jet apparatus (LVJA). Existing thermophysical models make it possible to calculate nozzles, which, in their shape, are close to Laval nozzles. They also allow for determining the position of the outlet cross-sectional area of the nozzle, where the flow separation from the channel walls occurs. However, these models do not allow for profiling the nozzle’s supersonic part, which does not make it possible to ensure the maximum efficiency of the vaporization process. Therefore, in the presented article, the available thermophysical model was improved significantly, which made it possible to obtain the profile of the supersonic part of the nozzle. As a result, a geometric shape that ensures the highest efficiency of the outflow process can be chosen for the primary flow at specified initial and final thermodynamic parameters. According to the calculation results and the proposed methodology, parameters were distributed along the nozzle for the primary flow. Also, efficiency indicators of the outflow of the boiling liquid underheated to saturation were achieved for the different geometric shapes. Mathematical modeling of the operating process in the motive nozzle using ANSYS CFX 2004 R1 (ANSYS, Inc., Canonsburg, PA, USA) was performed to prove the reliability of the results. Also, a comparative analysis of the obtained calculation and simulation results for nozzles with a profiled supersonic part and straight walls was carried out. To assess the expediency of profiling the supersonic part of the nozzle for the primary flow at the LVJA, a comparison of analytical modeling and numerical simulation results with the experimental studies was carried out for nozzles with straight walls. Finally, the velocity ratios of nozzles with profiled supersonic parts and straight walls were obtained. This allowed for rational choosing of the nozzle shape to ensure the highest vaporization efficiency.